2022
DOI: 10.3390/ijms232112748
|View full text |Cite
|
Sign up to set email alerts
|

Live or Heat-Killed Lactobacillus rhamnosus Aerosolization Decreases Adenomatous Lung Cancer Development in a Mouse Carcinogen-Induced Tumor Model

Abstract: An immunosuppressive microenvironment in lung concurs to pre-malignant lesions progression to cancer. Here, we explore if perturbing lung microbiota, which contribute to immunosuppression, by antibiotics or probiotic aerosol interferes with lung cancer development in a mouse carcinogen-induced tumor model. Urethane-injected mice were vancomycin/neomycin (V/N)-aerosolized or live or dead L. rhamnosus GG (L.RGG)-aerosolized, and tumor development was evaluated. Transcriptional profiling of lungs and IHC were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…For example, Zhang et al 41 found in their in vivo studies that Lactobacillus casei inhibited the proliferation of A549 lung cancer cells, and Matsuzaki T et al 42 found that the same species significantly improved the antitumor activity in mouse models of lung cancer. Le Noci et al 43 demonstrated that aerosol inhalation of Lactobacillus rhamnosus inhibited lung cancer growth by promoting local immunity. Lachnospiraceae can produce a large number of short-chain fatty acids that regulate the body's immune response 44 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al 41 found in their in vivo studies that Lactobacillus casei inhibited the proliferation of A549 lung cancer cells, and Matsuzaki T et al 42 found that the same species significantly improved the antitumor activity in mouse models of lung cancer. Le Noci et al 43 demonstrated that aerosol inhalation of Lactobacillus rhamnosus inhibited lung cancer growth by promoting local immunity. Lachnospiraceae can produce a large number of short-chain fatty acids that regulate the body's immune response 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that at the genus level, Lactobacillus and Bacillus were persistently increased significantly in the TRF group, which have been proven to have effective antitumor activity [ 44 , 45 ]. Lactobacillus administration conferred a beneficial role in lung cancer and colon cancer [ 46 , 47 ]. Moreover, the relative abundances of Bifidobacterium and Corynebacterium decreased in lung cancer mice and were recovered after TRF intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that Lactobacillus, one of the most widely studied probiotics in lung cancer, can significantly inhibit metastasis of tumor cells to the lung, thereby improving the prognosis of patients with lung cancer (39,40). A previous study by Valentino Le Noci et al suggested that an increase in the gene encoding the joining chain (J chain) of immunoglobulins was observed by Lactobacillus aerosolization, while high levels of Jchain mRNA strongly associated with a good prognosis for patients with lung adenocarcinoma (41). In addition, intravenous and intradermal injections of Lactobacillus casei significantly increased the anti-tumor activity in lung cancer model mice (42).…”
Section: Evolution Of Research Hotspots and Frontiersmentioning
confidence: 97%